Product Development using Kansei Engineering to Re-design New Food Packaging - Nanang Fatchurrohman; Mutiara Yetrina; Rifki Muhida; Anggi Hidayat (Jurnal Teknologi, 2022)
In the era of high market competition, product development must implement excellent innovation and responsiveness toward customer needs. One of the tools that had been successfully applied to support this objective is Kansei Engineering. Kansei is a Japanese word that refers to perception, impression, and feeling. Kansei Engineering is the process to collect product information based on the psychological emotions and feelings of customers. These represent customers' general impressions and emotions towards certain products or services which are then translated into characteristic designs. In this research, the researcher uses the Kansai engineering is applied to design new packaging for West Sumatra Sanjai Chips produced by local small-medium enterprise (SME). In processing the data, the researcher carried out a sampling technique, determining the number of respondents with the number of respondents being 100 in the first stage and 15 respondents in the second stage. From the first stage, eight Kansei words were collected. Followed by the second stage which was able to classify the most significant Kansei words based on the customer opinions. It was demonstrated from the investigation that new packaging was designed. With the new design it is expected that customers will become more aware and attracted to purchase the product.